Surgical Management of Giant Prolactinomas: A Descriptive Study - Michelle D. Lundholm; Divya Yogi-Morren; Kevin M. Pantalone; Pablo F. Recinos; Varun R. Kshettry; Pratibha P. R. Rao (International Journal of Endocrinology)
Introduction. Giant prolactinoma (GP) is a rare pituitary lactotropic cell tumor larger than 4 cm in its widest dimension, and is less likely than a smaller prolactinoma to achieve prolactin normalization on dopamine agonist (DA) monotherapy. There is a paucity of data on the circumstances and outcomes of second-line management of GP with surgery. Herein, our institution’s experience with the surgical management of GPs is described. Methods. A single-center retrospective analysis was conducted of patients who underwent surgery for giant prolactinoma from 2003 to 2018. A chart review was conducted for demographic data, clinical features, laboratory and radiographic findings, operative and pathology reports, perioperative management, and clinical outcomes in follow-up. Descriptive statistics were used. Results. Of 79 prolactinoma cases, 8 patients had GP with a median age of 38 years (range 20–53), 75% (6/8) were male, with a median largest tumor dimension of 6 cm (range 4.6–7.7), and a median prolactin level of 2,500 μg/L (range 100–>13,000). Six patients had transsphenoidal surgery for dopamine agonist (DA) resistance or intolerance. Two patients had a craniotomy for a missed diagnosis; one was due to the hook effect. No tumor resections were complete by either surgical approach; all had persistent hyperprolactinemia requiring postoperative DA therapy, and two patients had an additional craniotomy procedure for further tumor debulking. There was no recovery of pituitary axes and postoperative deficits were common. Remission as defined by prolactin normalization occurred in 63% (5/8) at a median time of 36 months (range 14–63 months) on DA therapy after surgery with a follow-up of 3–13 years. Conclusions. GPs infrequently require surgical resection, which is generally incomplete and requires adjuvant therapy. Given the rarity of surgery for GPs, multi-institutional or registry studies would yield clearer guidance on optimal management.